Penerapan Metode QCC untuk Mempersingkat Waktu Perbaikan Sistem Lubrikasi Mesin Robodrill di PT XYZ - Aliyudin, Kusdian; Setijadi, Setijadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The automotive manufacturing industry demands high levels of effectiveness and efficiency in every production process, particularly through the reliability of Robodrill machines, which play a crucial role in precision machining. Problems in the lubrication system frequently lead to high downtime, resulting in production delays, reduced productivity, and increased operational costs. Based on historical maintenance data from 2022 to 2024 at PT XYZ, the repair time for the Robodrill lubrication system showed significant fluctuations, ranging from 27 to 227 minutes, causing the maintenance division to fail in achieving its Key Performance Indicators (KPI). This study aims to identify the main factors contributing to prolonged repair times, design and implement effective improvement solutions, and evaluate the impact of the Quality Control Circle (QCC) method on maintenance performance. The QCC approach was applied through root cause analysis using fishbone diagrams, Pareto charts, and the 5W+1H method. The results indicate that the implementation of QCC successfully reduced repair time, minimized machine downtime, improved technician effectiveness, and supported the sustainable achievement of maintenance KPI.